2022
DOI: 10.3390/biom12060820
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Lymphangiogenesis in Peripheral Nerve Autografts Contrasts Schwann Cell-Induced Apoptosis of Lymphatic Endothelial Cells In Vitro

Abstract: Peripheral nerve injuries pose a major clinical concern world-wide, and functional recovery after segmental peripheral nerve injury is often unsatisfactory, even in cases of autografting. Although it is well established that angiogenesis plays a pivotal role during nerve regeneration, the influence of lymphangiogenesis is strongly under-investigated. In this study, we analyzed the presence of lymphatic vasculature in healthy and regenerated murine peripheral nerves, revealing that nerve autografts contained in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Our study was also among the first [ 49 , 77 , 92 , 93 ] to shine light on the involvement of lymphatic vasculature and lymphangiogenesis, respectively, in peripheral nerve repair and regeneration. Interestingly, we found that the number of lymphatics was drastically increased in both ANGs and MCVs following median nerve reconstruction.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Our study was also among the first [ 49 , 77 , 92 , 93 ] to shine light on the involvement of lymphatic vasculature and lymphangiogenesis, respectively, in peripheral nerve repair and regeneration. Interestingly, we found that the number of lymphatics was drastically increased in both ANGs and MCVs following median nerve reconstruction.…”
Section: Discussionmentioning
confidence: 98%
“…We hypothesize that this observation can be explained by a study recently published by our group. In this work, we showed for the first time that Schwann cells induce apoptosis of lymphatic endothelial cells when cocultured in vitro via extended filopodia-like protrusions [ 49 ]. While this, on the one hand, explains the absence of lymphatic vessels inside uninjured murine peripheral nerves, these findings can be further extrapolated to the findings in the study at hand.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peripheral nerves (PNs) are highly specialized organs that connect the central nervous system through motor, sensory or autonomic pathways, with distal target organs ( Carriel et al, 2014 ). Histologically, PNs are composed to two well-defined tissues, the parenchyma or functional unit, formed by peripheral nerve fibers (PNFs), and the stroma or structural unit, formed by three specialized layers of connective tissue (the epineurium, the perineurium and the endoneurium) that provide blood and lymphatic vessels, and confer the structural and biomechanical properties to these essential organs ( Geuna et al, 2009 ; Hromada et al, 2022 ). Due to their wide anatomical distribution PNs are often affected by traumatic injuries of diverse nature or iatrogenic injuries during surgical procedures ( Robinson, 2000 ).…”
Section: Introductionmentioning
confidence: 99%